2012
DOI: 10.1128/mcb.00717-12
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interaction between TRAF6 and Notch Signaling Regulates Adult Myofiber Regeneration upon Injury

Abstract: Skeletal muscle is a postmitotic tissue that repairs and regenerates through activation of a population of stem-cell-like satellite cells. However, signaling mechanisms governing adult skeletal muscle regeneration remain less understood. In the present study, we have investigated the role of tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6), an adaptor protein involved in receptor-mediated activation of multiple signaling pathways in regeneration of adult myofibers. Skeletal musclespecific deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 67 publications
(135 reference statements)
5
56
2
Order By: Relevance
“…Ablation of TRAF6 did not have any major effect on the phosphorylation of Akt kinase and p38MAPK (84). While these data are in contrast to previous reports of TRAF6-dependent activation of Akt (36) and p38MAPK (101), they highlight TRAF6-mediated differential activation of downstream signaling pathways (102).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Ablation of TRAF6 did not have any major effect on the phosphorylation of Akt kinase and p38MAPK (84). While these data are in contrast to previous reports of TRAF6-dependent activation of Akt (36) and p38MAPK (101), they highlight TRAF6-mediated differential activation of downstream signaling pathways (102).…”
Section: Discussioncontrasting
confidence: 56%
“…Studies from our lab has also shown that blocking TRAF6 in differentiated myofibers inhibits the activation of NF-B and increases levels of promyogenic M2c macrophages in regenerating skeletal muscle potentially through a cross-talk with Notch pathway (84). This suggests that the inhibition of TRAF6 limits the levels of inflammatory cytokines which hastens the appearance of M2c macrophages resulting in increased proliferation of myogenic cells and rapid restoration of myofibers architecture.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations